Proportionality trumps gentleness: reforming Block’s evictionism (part I) - Ayres, Cedric John (Revista de Investigações Constitucionais, 2021)
This paper argues against the most important theoretical foundations which Walter Block uses to defend his thesis that Evictionism legitimizes indirectly deadly evictions of a progeny while simultaneously forbidding abortion. It begins by presenting Block’s Gentleness principle and Rothbard’s principle Proportionality separately. Then, it compares both principles to analyze how satisfactorily each of them deals with some important general problems of libertarian legal theory. The ‘bubble gum theft’ scenario is the main tool for this comparison because both authors uses ‘petty theft’ examples to illustrate their respective principles. This paper’s conclusions are as follows: First, every moment of crime is interconnected. Second, proportionality applies to every moment of crime. Third, that Block’s so-called ‘gentleness principle’ is not only redundant to proportionality, but also cannot be a libertarian principle for two reasons: (1) it implies positive rights and obligations; (2) it presupposes a deterrence penology. This paper is the first in a series of three in an attempt to reform the standard libertarian stance on abortion.